Comparative Evaluation of an Alternative Treatment for Erectile Dysfunction (Texas Journal of Medical Science, 2022)
Erectile dysfunction (ED) in men is defined as the persistent inability to achieve and maintain an erection sufficient for successful intercourse. [9] Although ED is a mild disorder, it is associated with mental and psychosocial health and significantly affects both the patient and his partner and family. ED affects 10- 25% of middle-aged and elderly men. The demographic features of modernity, the emergence and popularization of new methods of treatment, a more tolerant attitude of patients and society towards the problem of ED have led to the fact that today it is detected more often, and healthcare costs are growing accordingly. Erectile dysfunction causes serious damage to the emotional and mental well-being of men, but many of them are hesitant to share their problem with others, and this should be dealt with by a doctor. The Massachusetts Study of Male Aging (2011) showed that 52% of men aged 40-70 years have a sexual dysfunction: 10% of respondents complained of complete erectile dysfunction, 25% of moderate and 17% of mild erectile dysfunction